2020
DOI: 10.24059/olj.v24i1.1956
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Programming Expertise in a Web-based E-learning Paradigm

Abstract: Modern internet technologies have revolutionized the traditional education by providing flexible and resourceful e-learning opportunities in all the fields of knowledge. Programming constitutes integral part of undergraduate curriculum in computer sciences, and adequate level of programming expertise is expected from the graduates. In this paper, we explore and examine key factors that contribute to developing programming skills among undergraduate students in e-learning. These factors include teaching practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 38 publications
0
6
1
Order By: Relevance
“…Besides that, personal traits and attitudes play an important role in determining the intrinsic motivation. Negative personal belief and perception on the difficulties in learning of computer programming have contributed to the failure in learning of computer programming (Ng & Bereiter, 1991;Qian & Lehman, 2017;Rafique et al, 2020;Robins, 2019). This is due to the passing of comments, opinions, and suggestions from their senior peer which has taken the subjects before (Jenkins, 2002).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides that, personal traits and attitudes play an important role in determining the intrinsic motivation. Negative personal belief and perception on the difficulties in learning of computer programming have contributed to the failure in learning of computer programming (Ng & Bereiter, 1991;Qian & Lehman, 2017;Rafique et al, 2020;Robins, 2019). This is due to the passing of comments, opinions, and suggestions from their senior peer which has taken the subjects before (Jenkins, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Hence, bearing the negative impression and wrong perspective toward programming subjects leads the students to make their own conclusion that programming is an extremely difficult subject. It impaired the intrinsic motivation of the student which created a negative impact on their attitude to continue learning for success (Ng & Bereiter, 1991;Qian & Lehman, 2017;Rafique, Dou, Hussain, & Ahmed, 2020;Robins, 2019). However, there is research that shows using screencasting in teaching and learning of programming could increase the positive attitude towards the learning of programming (Cheah, 2019).…”
Section: Negative Perceptionmentioning
confidence: 99%
“…Safsouf et al [34] concluded that the perceived ease of use and usefulness have a significant impact on behavior intention, and this conclusion is similar to the results of related TAM studies. Rafique et al [49] found through research that perceived usefulness positively affects the behavioral participation intention to learn online. Based on the above analysis, the hypotheses proposed in this study are as follows:…”
Section: Hypothesismentioning
confidence: 99%
“…At the same time, perceived usefulness partly mediates the impact of perceived ease of use on the attitude of participation. Therefore, perceived usefulness is also an essential factor influencing behavior intention [29,47,49]. For the development of online education courses, it is necessary to work hard and improve the content quality of the courses, so that university students can perceive those online courses as conducive to improving their learning efficiency, enhancing learning effects, and learning more knowledge, making learning more enjoyable and relaxing.…”
Section: Perceived Usefulnessmentioning
confidence: 99%
“…Alkhalaf et al (2018) defined Information Quality was defined as including the scientific and pedagogical content of the information to be taught or the scientific content in general. But the study of Vululleh, P. (2018) and the study ofRafique et al (2020) concluded that student's behavioral intention to use e-learning was significantly influenced by the following factors; Quality of life, Perceived ease of use, Perceived usefulness, Social influence[5],[17].The study of Vululleh, P. (2018) conducted the ETAM model by incorporating 2 motivation attributes; social influence and quality of life in Liberia on 269 students whereas the study of Rafique et al (2020) conducted the Technology Acceptance Model (TAM) on a sample of 460 undergraduate students (Software Engineering and Bachelor of Computer Science). Both of these studies disclosed that learning intentions greatly impacted by the conducted factors.…”
mentioning
confidence: 99%